2022
DOI: 10.1017/ipm.2022.15
|View full text |Cite
|
Sign up to set email alerts
|

Service user satisfaction with care in a specialist service for young people with attention deficit hyperactivity disorder

Abstract: Objectives: Consumer satisfaction is considered one of the most important measures of service quality in child mental health; however, there is limited understanding of factors that influence satisfaction. The objective of this study was to investigate key factors influencing satisfaction with care (SWC) in ADMiRE, a specialist service for young people (YP) with attention deficit hyperactivity disorder (ADHD). Methods: Parents/carers (n = 67) and YP > 9 years (n = 44) attending ADMiRE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…Similar to most studies, 5 , 31 , 51 both groups generally reported high levels of satisfaction with CAMHS, with parents being significantly more satisfied than adolescents. Nevertheless, compared to previous findings, 3 , 5 , 49 only a modest proportion (6%–8%) of the variance in predictors of parent user satisfaction was explained by the models.…”
Section: Discussionsupporting
confidence: 81%
“…Similar to most studies, 5 , 31 , 51 both groups generally reported high levels of satisfaction with CAMHS, with parents being significantly more satisfied than adolescents. Nevertheless, compared to previous findings, 3 , 5 , 49 only a modest proportion (6%–8%) of the variance in predictors of parent user satisfaction was explained by the models.…”
Section: Discussionsupporting
confidence: 81%
“…Studies, like one conducted with 497 adolescents in Atlantic Canada, shed light on the apparent inconsistency between high engagement with mental health services and lower mental health outcomes. Findings suggest that quality interactions, especially those fostering a strong therapeutic alliance [197], were more indicative of future mental health improvements than merely the quantity of services received [198]. This finding of higher mental health services utilization with lower well-being outcomes warrants future investigation in New Brunswick.…”
Section: Mental Health Service Utilizationmentioning
confidence: 87%
“…A direction for future research is surveying and interviewing children and adolescents themselves on their views of telehealth. Parents, and children and adolescents with ADHD, may have differing opinions of health services [39], so it is important to understand both views to provide patient-centred care. For example, it is acknowledged that adolescents may experience additional complexities using telehealth in terms of maintaining privacy and confidentiality [31,40].…”
Section: Implications For Practice and Researchmentioning
confidence: 99%